STEEL ROOF REDESIGN USING HYBRID SINGLE BARREL VAULT: STRUCTURAL EFFICIENCY THROUGH LRFD AND VALUE ENGINEERING - Sahira Widyarahayu; Nawir Rasidi (Jurusan Teknik Sipil Politeknik Negeri Malang, 2025)
Roof structure is one of the important elements in a building, there are many types of roof structures such as Portal Frame. Using steel pipe as a portal frame will cause higher dimensions to resist the flexural moment, since it is categorized as a compression member. This research focuses on redesigning materials used with WF profile and modification of castellated beam to optimize the dimension of profile and reducing the cost of portal frame roof that uses steel pipe. By applying Value Engineering Method to analyze the cost and LRFD Method to analyze the structure, the most effective alternative design can be implemented at Rawamangun Station, LRT Jakarta Project, as the place of the research. Alternative materials considered are Hybrid Castellated with WF Solid, Full Castellated Beam and Full WF Solid. After going through many processes of analyzing, the alternative material chosen is Hybrid Castellated Beam with WF Solid based on the fulfilled structural aspects, workability considerations and optimum cost. It is obtained that the alternative model cost Rp. 7,110,683,434.77, while the existing design cost Rp. 17,588,537,219.38. So, the alternative model successfully reduces the cost of existing model up to 40.43% without changing the function of the building structure.